Pertimbangan Hakim dalam Penjatuhan Uqubat Jarimah Pelecehan Seksual terhadap Anak di Aceh (Analisis Putusan No 8/Jn/2020/MS.Ttn) - Achmad Fikri Oslami (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Aceh is one of the provinces that has a high number of cases of sexual violence against women and children. The Syar'iyah Court is a court within the Religious Courts which hears cases related to sexual crimes including sexual harassment, adultery, and rape as regulated in Qanun number 6 of 2014 concerning Jinayat Law. Ideally, the punishment or 'uqubat for child sexual abuse in the jinayat law is at least the same as the child protection law or heavier with the increasing number of cases of sexual abuse of both women and children. This paper was written to find out what things are considered by the Panel of Judges of the Syar'iyah Court on cases of sexual violence against children in Aceh by analyzing decision number 8/JN/2020/MS.Ttn so that it can provide an ideal picture. Jinayat law enforcement image. especially in cases of child sexual abuse. This research is a type of normative research using a case approach, carried out using case studies related to the issues at hand which have become court decisions with permanent legal force, related to the themes discussed which were obtained from primary materials in the form of decisions at the level of The first was tried by the Panel of Judges of the Tapaktuan Syar'iyah Court number 8/JN/2020/MS.Ttn, then the appeal decision of the Aceh Syar'iyah Court Judges number 17/JN/2020/MS.Aceh and the last was the Supreme Court's cassation decision number 11 K/AG/JN/2020. The results of this study need a minimum penalty for sexual abuse against children due to its special handling and has become a serious problem in Indonesia, so that there is no uqubat disparity imposed between the Syar'iyah Courts in Aceh.